Inter-war Penal Policy and Crime in England - Brown, A. author. aut Link
IX, 191 p.
Keywords: An exploration of the 1932 prison riot in Dartmoor Convict Prison. One of the most notorious and destructive in English prison history, it received unprecedented public and media attention. This book examines the causes, events and consequences to shed new light on prison cultures and violence as well as penal policy and public attitudes.